Incorporation of bimetallic nanoparticles in mesoporous TiO₂ for hydrogen evolution reaction - Sheah, Dai Rong (Nanyang Technological University, 2023)
Photocatalytic hydrogen evolution reaction (HER) is a promising method for generating sustainable energy, but the commonly used photocatalyst mesoporous TiO2 has limited efficiency for HER due to its low surface area, large bandgap, and limited charge carrier mobility. To overcome these limitations, we explored the addition of metallic nanoparticles, which act as cocatalysts to improve the efficiency of HER. However, optimizing the properties of mesoporous TiO2 is challenging due to the interplay between various parameters such as precursor, loading weight, ratio of metallic nanoparticles, and thermal treatment conditions. Our study aims to address this challenge by exploring these key parameters to optimize the properties of mesoporous TiO2 and enhance its performance in HER. We synthesized mesoporous TiO2 and characterized its surface area, pore size, and XRD phase, exploring parameters such as the precursor used, loading weight, ratio of Cu to Ru, and solvothermal temperature to optimize its properties. Our findings showed that the best results were obtained with a Cl- precursor and a loading weight of 4 mol% CuRu/TiO2 with Cu and Ru in a 1:1 ratio, with optimal solvothermal temperature of 140 °C. The resulting catalyst exhibited a surface area of 121.8 m²/g and a pore size distribution centered at 6.8 nm, and the HER activity for best CuRu/TiO2 sample were 1184.2 umol ∙ g-1∙h-1 . Our study highlights the importance of optimizing the properties of mesoporous TiO2 to enhance its efficiency in HER, a promising approach for generating sustainable energy. By contributing to the fundamental understanding of the synthesis and optimization of mesoporous TiO2, our findings can be applied in various fields, including catalysis, energy conversion, and environmental remediation, to address critical challenges faced by society today. Our research holds great potential for designing and developing new materials with improved performance, contributing to the development of sustainable energy solutions.